Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae): a second species of Hypolepida Britton, 1978 - Allsopp, Peter G. (Zootaxa, 2020)
The genus Hypolepida Britton, 1978 (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini), is reviewed and a second species, H. braes new species, is described and differentiated from H. wilsoni Britton, 1978. Both species occur in northeastern Queensland, with the former in dry-tropical open forest and the latter in wetter areas closer to the coast.